1981
DOI: 10.1080/00288233.1981.10420876
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of black beetle,Heteronychus arator(Coleoptera: Scarabaeidae)—Population studies

Abstract: The dynamics of populations of black beetle, Heteronychus arator (F.), in plots of paspalum (Paspalum dilatatum Poir), ryegrass (Lolium perenne L.), and ryegrass/white clover (Trifolium repens L.) pastures were studied. Life tables were constructed which quantified individual and generation mortalities and identified the key factors causing population change. The important components were variation in natality, summer mortality, and winter-spring disappearance. Investigation of the density relationships ofthe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
0
23
2
Order By: Relevance
“…Furthermore, the discrepancy in larval survival found in our study could be explained by the higher moisture sensitivity of first‐instar larvae than of eggs (King et al. ), but very wet soil also hosted few eggs. Although the later observation contrasts a report by Logan , a similar finding obviously demonstrated that decomposing plant residues are associated with lower number of eggs than decomposing cow manure (Fig.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, the discrepancy in larval survival found in our study could be explained by the higher moisture sensitivity of first‐instar larvae than of eggs (King et al. ), but very wet soil also hosted few eggs. Although the later observation contrasts a report by Logan , a similar finding obviously demonstrated that decomposing plant residues are associated with lower number of eggs than decomposing cow manure (Fig.…”
Section: Discussioncontrasting
confidence: 74%
“…Both temperature and moisture are critical factors governing population change, with early larval instars being the most sensitive of the life stages to these factors. Cumulative thermal units above 15°C in spring are directly related to summer larval survival, while high soil moisture in spring and early summer adversely affect early stage larval survival (King et al 1981a(King et al , 1981b. Warm temperatures also accelerate larval development leading to early adult emergence which allows the beetles a longer period for accumulating fat before winter.…”
Section: Life Cycle and Biologymentioning
confidence: 99%
“…In the northern half of the North Island these four pest species are often sympatric. Costelytra zealandica and H. arator are univoltine species (Henzell et al 1980;King et al 1981), S. lepidus is bivoltine (Gerard et al 1999) while N. lecoloma takes 8-24 months to complete a generation (Hardwick 1999). Heteronychus arator, C. zealandica and S. lepidus disperse away from previously occupied areas by flights occurring in autumn, spring and summer respectively (Henzell et al 1980;Watson 1980;Addison & Hardwick, unpubl.…”
Section: Introductionmentioning
confidence: 99%